2009
DOI: 10.1001/archoto.2009.93
|View full text |Cite
|
Sign up to set email alerts
|

Ecthyma Gangrenosum

Abstract: Ecthyma gangrenosum (EG) is a recognized cutaneous infection commonly associated with Pseudomonas aeruginosa bacteremia. It typically occurs in patients who are septic and severely immunocompromised. Clinical presentation characteristically begins as an erythematous or hemorrhagic vesicle or bulla, which evolves into a necrotic ulcer with eschar and surrounding erythema. This was first described in association with Pseudomonas septicemia by Barker in 1897 and was later given the name "ecthyma gangrenosum" by H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A weak mechanical defense barrier and underdeveloped cellular or humoral immunity increased the risk of infection in newborns [ 4 , 5 ]. In the general population lesions are usually present in the gluteal and perineal regions or on the extremities and trunk, but rarely are they found on the face or neck [ 6 ], whereas, in most reported cases of preterm EG, the face is affected as was the case in our patient [ 7 , 8 ]. Even though literature has shown that most children with EG had either previously undetected immunodeficiencies or transient risk factors such as immunosuppressive therapy that predisposed them to the development of the disease, not many newborn cases have been reported [ 9 ].…”
Section: Discussionmentioning
confidence: 72%
“…A weak mechanical defense barrier and underdeveloped cellular or humoral immunity increased the risk of infection in newborns [ 4 , 5 ]. In the general population lesions are usually present in the gluteal and perineal regions or on the extremities and trunk, but rarely are they found on the face or neck [ 6 ], whereas, in most reported cases of preterm EG, the face is affected as was the case in our patient [ 7 , 8 ]. Even though literature has shown that most children with EG had either previously undetected immunodeficiencies or transient risk factors such as immunosuppressive therapy that predisposed them to the development of the disease, not many newborn cases have been reported [ 9 ].…”
Section: Discussionmentioning
confidence: 72%
“…In the second nonbacteremic form, the lesions occur at the site of direct inoculation into the skin. Pseudomonas aeruginosa produces protease, elastase, phospholipase C, and exotoxin A that are responsible for the direct tissue and vessel destruction leading to ulcerative lesions [5,8,9] . Mesenchymal Stem Cells (MSCs) are one type of stem cells that can differentiate into a variety of tissue-specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in association with Pseudomonas septicemia by Barker in 1897 and was later given the name “ecthyma gangrenosum” by Hitschmann and Kreibich. [ 1 ] It is usually seen in critically ill patients with neutropenia or underlying immune deficiency who present with skin lesions that begin as an erythematous, nodular or hemorrhagic vesicles that turn into necrotic ulcers with eschar formation. [ 2 ] The skin lesions are usually widespread over the area involved.…”
Section: Introductionmentioning
confidence: 99%